Development of capillary dysfunction in Alzheimer’s disease - Vorobev, S.; Yanishevskiy, S.; Efimtsev, S.; Sokolov, A.; Dyachuk, V. (Frontiers in Aging Neuroscience, 2024)
Alzheimer’s disease (AD) is currently considered the major cause of cognitive impairment in older adults. This explains the close attention to the issue of AD research. The pathomorphological basis of the disease is a neurodegenerative process, the early stages of which are formed in the hippocampus and the morphofunctionally deep parts of the temporal lobes of the brain closely related to it. Several hypotheses have been advanced concerning the causes of neurodegeneration: the amyloid hypothesis, the calcium homeostasis impairment hypothesis, the inflammatory hypothesis, and the prion hypothesis. However, these hypotheses cannot explain the early stages of the pathogenesis of neurodegenerative diseases, in particular Alzheimer’s disease. This health problem requires further comprehensive study of available data, as well as additional investigations to determine the nature of such a process. In this review, the data on microcirculatory disorders in the capillaries of the hippocampus and mediobasal structures of the temporal lobes of the brain, which may be an initiating factor that triggers neurodegenerative events, are analyzed.